Gambaran Karakteristik Pasien Hipertensi di Puskesmas Kalipucang - Zulfi Noor Fadia; Titik Respati; Wida Purbaningsih (UNISBA Press, 2023)
Abstract. Hypertension is a complex disease because it can damage many organ systems. The prevalence of hypertension in Indonesia is still increasing until now. The increase in cases is due to hypertension being a multifactorial disease. The risk factors for hypertension are classified as modifiable and non-modifiable. Therefore, researchers are interested in studying the description of the characteristics of hypertensive patients at the Kalipucang Health Center. This study used an analytic observational method with a cross-sectional design. The sampling technique is consecutive sampling. Patient data was taken from the Kalipucang Health Center medical records. Obtained data on hypertension patients as many as 129 patients. The results showed that the majority of hypertension patients at the Kalipucang Health Center were aged ≥60 (68.2%), women (93.8%), obesity 1 (35.7%), and stage 1 hypertension (46.5%). It was concluded that the characteristics of hypertension patients at the Kalipucang Health Center were ≥60 years old, female, obese 1, and had stage 1 hypertension. Abstrak. Hipertensi adalah penyakit yang bersifat kompleks karena dapat merusak banyak sistem organ. Sampai saat ini prevalensi kejadian hipertensi di Indonesia masih terus meningkat. Peningkatan kasus disebabkan karena hipertensi merupakan penyakit yang bersifat multifaktorial. Faktor risiko hipertensi dibedakan menjadi dapat dimodifikasi dan tidak dapat dimodifikasi. Oleh karena itu peneliti tertarik untuk meneliti tentang gambaran karakteristik pasien hipertensi di Puskesmas Kalipucang. Penelitian ini menggunakan metode observasional analitik dengan desain cross-sectional. Teknik pengambilan sampel yaitu dengan consecutive sampling. Data pasien diambil dari data rekam medis di Puskesmas Kalipucang sehingga diperoleh data pasien hipertensi sebanyak 129 pasien. Hasil menunjukan bahwa mayoritas pasien hipertensi di Puskesmas Kalipucang berusia ≥60 (68,2%), Wanita (93,8%), Obesitas 1 (35,7%), dan hipertensi stage 1 (46,5%). Disimpulkan bahwa gambaran karakteristik pasien hipertensi di Puskesmas Kalipucang adalah berusia ≥60, wanita, obesitas 1, dan memiliki hipertensi stage 1.